Production of cloned mice using oocytes derived from ICR-outbred strain. Issue 6 (December 2017) - Tanabe, Yoshiaki; Kuwayama, Hiroki; Wakayama, Sayaka; Nagatomo, Hiroaki; Ooga, Masatoshi; Kamimura, Satoshi; Kishigami, Satoshi; Wakayama, Teruhiko
Abstract : Recently, it has become possible to generate cloned mice using a somatic cell nucleus derived from not only F1 strains but also inbred strains. However, to date, all cloned mice have been generated using F1 mouse oocytes as the recipient cytoplasm. Here, we attempted to generate cloned mice from oocytes derived from the ICR-outbred mouse strain. Cumulus cell nuclei derived from BDF1 and ICR mouse strains were injected into enucleated oocytes of both strains to create four groups. Subsequently, the quality and developmental potential of the cloned embryos were examined. ICR oocytes were more susceptible to damage associated with nuclear injection than BDF1 oocytes, but their activation rate and several epigenetic markers of reconstructed cloned oocytes/embryos were similar to those of BDF1 oocytes. When cloned embryos were cultured for up to 4 days, those derived from ICR oocytes demonstrated a significantly decreased rate of development to the blastocyst stage, irrespective of the nuclear donor mouse strain. However, when cloned embryos derived from ICR oocytes were transferred to female recipients at the two-cell stage, healthy cloned offspring were obtained at a success rate similar to that using BDF1 oocytes. The ICR mouse strain is very popular for biological research and less expensive to establish than most other strains. Thus, the results of this study should promote the study of nuclear reprogramming not only by reducing the cost of experiments but also by allowing us to study the effect of oocyte cytoplasm by comparing it between strains.